Reinstatement of Squilla Steinh., a priority name against the illegitimate Charybdis Speta (Hyacinthaceae, Urgineoideae) - Mario Martínez-Azorín; Manuel B. Crespo; María Ángeles Alonso-Vargas (Mediterranean Botany, 2022)
Squilla Steinh. was considered to be an orthographic variant of Scilla L., and therefore the new genus Charybdis Speta was created to include Scilla maritima L. and related taxa occurring in the Mediterranean. Molecular phylogenetic studies recovered Charybdis as distant from Urginea; this finding was also supported by morphology and phytochemistry data. However, after typification of Scilla using S. maritima by Rafinesque, Charybdis became illegitimate under Art. 52 of the Shenzhen Code as its name became superfluous when published. A binding decision was requested from the Nomenclature Committee for Vascular Plants (NCVP) on whether Scilla L. and Squilla Steinh. are sufficiently alike to be considered orthographic variants and, hence, to be confused. Most members of the committee favour treating Squilla as not confusable with Scilla, which leaves the former name available for the current concept of Charybdis. In this context, we reevaluate the taxonomy of the genus, accepting 12 species of which eight are accommodated in Squilla as new combinations. Conversely, one of the species of Charybdis is transferred here to Urginavia. Nomenclatural types (including designation of 13 lectotypes, one neotype and one epitype) and the most relevant synonyms are given for each accepted taxon. An identification key is also presented for Squilla to assist future taxonomic studies in this group. We also include a revision of the taxonomic circumscription of the taxa related to S. undulata.